2010
DOI: 10.1007/s00228-010-0932-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends in opioid analgesics consumption, Israel, 2000–2008

Abstract: There has been a modest increase in opioid consumption in the years 2000-2008. This has been associated with substantial changes in the pattern of differential opioid prescribing characterized by increased prescription of oxycodone, fentanyl, buprenorphine, and dextropropoxyphene, and decreases in morphine, pethidine, and codeine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 15 publications
6
27
0
Order By: Relevance
“…Fentanyl and morphine sales (Figure 2) were comparable to that of other European Countries,22 and almost superimposable to data observed in Nordic Countries7 and Israel 23. The sales of fentanyl increased from 0.011 to 0.468 DDDs/day/1000 inhabitants between 2000 and 2010, whereas morphine sales decreased from 0.113 to 0.084 DDDs/day/1000 inhabitants in the same period (Figure 2).…”
Section: The Effect Of Technological Innovationsupporting
confidence: 77%
“…Fentanyl and morphine sales (Figure 2) were comparable to that of other European Countries,22 and almost superimposable to data observed in Nordic Countries7 and Israel 23. The sales of fentanyl increased from 0.011 to 0.468 DDDs/day/1000 inhabitants between 2000 and 2010, whereas morphine sales decreased from 0.113 to 0.084 DDDs/day/1000 inhabitants in the same period (Figure 2).…”
Section: The Effect Of Technological Innovationsupporting
confidence: 77%
“…The decreasing trend in pethidine use noted in Taiwan is consistent with previous reports from other nations (11,12),. Joranson et al (23) retrospectively surveyed the U.S. medical record database, which revealed a 35% decrease (5.2 to 3.4 million grams) in the medical use of pethidine from 1990 to 1996.…”
Section: Discussionsupporting
confidence: 91%
“…Gilson et al (22) also used the same database to demonstrate that there was a further decline in medical use of pethidine by over 6% (5.8 to 5.4 million grams) from 1997 through 2002. Additionally, in Israel from 2000 to 2008, pethidine consumption fell by 65%, from 0.07 to 0.02 DDD/1,000 inhabitants/day (12). However, two population-based surveys found that pethidine consumption was less than 0.01 DDD/1,000 inhabitants/day and remained constant in both Spain between 1992 and 2006 (11) and in the Slovak Republic between 1998 and 2002 (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2002 to 2006, the prescribing rate (DDDs) of oxycodone increased four times in Norway, while the rate doubled in Sweden and Finland [25]. From 2004 to 2006, the prescribing rate (DDDs) of oxycodone increased by 239% in Iceland [25], 94% in Italy [26] and 50% in Israel [27]. No studies have analysed why some physicians seem to have a preference for oxycodone, but some studies indicate that strategic pharmaceutical marketing and physicians' concern about addiction and abuse may have had an impact [28][29][30].…”
Section: Introductionmentioning
confidence: 99%